Estudio de factibilidad para la creación de un local de comida adelgazante para personas con sobrepeso en el cantón Ventanas, año 2013 - Vera Castillo, Marianela Mireya (2016)
This feasibility study aims to evaluate the economic profitability by implementing a local varied and specialized slimming meals, the viability of the project is the effected by an investment analysis and acceptance of the service, for which he developed a study on the needs of consumers who are overweight in the canton windows.The foregoing gives the tone to tap this great business opportunity that emerges in the market. For this to know that one of the basic needs of overweight people to eat is to prevent their weight continues to rise, which causes a number of diseases, so it is concluded to analyze the possibility of introducing to the market a Restaurant slimming meals. This proposal was ratified by a process from market research to a marketing plan to demonstrate the correctness or not of a potential business opportunity. Similarly, this project was based in relation to the background that relates to the generalities of the restaurants (and then gives the concept or idea of slimming restaurant meals, thus realizing it, the methodology to be followed where the general objective, specific objectives arises. Potential markets and acceptance of the service to be provided probed in this case a restaurant with varied diets. This research gives a real parameter to make the decision to go ahead with the development of the business or end with the expectations through concrete foundations of the population using an appropriate sample size, conducting surveys and replenishes the end of that investigation. Given the size of the project the investment required for the operation of the company is not very high, but especially the profitability is acceptable based on the following data: Rate Net Present Value (NPV) of 21,936.97, the Internal Rate of Return (IRR) with 32%andBenefit Cost Ratio (BC) 3.25.